2012
DOI: 10.1371/journal.pone.0048668
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimising the Production of and Expression from Polycistronic Vectors in Embryonic Stem Cells

Abstract: Polycistronic vectors linked by self-processing 2A peptides have been successfully used in cellular reprogramming. The expression of these vectors has yet to be well documented in embryonic stem cells. In the present study, we generated expression cassettes containing combinatorial arrangements of 3 pancreatic transcriptions factors (Pdx1, Nkx2.2 and Ngn3) together with an eGFP reporter, all linked by self-processing 2A peptides. The study tested the utility of constructing complex expression cassettes by liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In theory, the 2A-mediated polycistronic system allows for the production of multiple proteins at equimolar levels, as translation is carried out from a single polycistron, and peptides linked by 2A peptide are separated via a ribosome skipping mechanism. However, it should be noted that expression levels from 2A polycistronic constructs are dependent on the combined effects of various factors, including the number of transgenes, their relative positions in the construct, the order and types of 2A peptide, 2A coding sequences, as well as regulatory elements in the expression cassette (Donnelly et al, 2001a;de Felipe et al, 2010;Rothwell et al, 2010;Gao et al, 2012;Liu et al, 2017). With regards to the effects of transgene position, the results of this study are similar to those of a previous report which showed that no significant differences in transgene expression levels were observed when varying the positions within 2A polycistronic constructs in mouse embryonic stem cells (Gao et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In theory, the 2A-mediated polycistronic system allows for the production of multiple proteins at equimolar levels, as translation is carried out from a single polycistron, and peptides linked by 2A peptide are separated via a ribosome skipping mechanism. However, it should be noted that expression levels from 2A polycistronic constructs are dependent on the combined effects of various factors, including the number of transgenes, their relative positions in the construct, the order and types of 2A peptide, 2A coding sequences, as well as regulatory elements in the expression cassette (Donnelly et al, 2001a;de Felipe et al, 2010;Rothwell et al, 2010;Gao et al, 2012;Liu et al, 2017). With regards to the effects of transgene position, the results of this study are similar to those of a previous report which showed that no significant differences in transgene expression levels were observed when varying the positions within 2A polycistronic constructs in mouse embryonic stem cells (Gao et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This allowed fast pre-screening of homologous recombination events (see Materials and methods). Since it had previously been mentioned that linker sequences influence the expression of open reading frames connected by 2A peptides (Holst et al, 2006;Gao et al, 2012;Souza-Moreira et al, 2018), we tested different linker versions. We compared assemblies without linker (no linker; NL) with those comprising a short GSG linker sequence (L1) and a longer version of 18 amino acids (L2).…”
Section: Establishing a Reporter System For Screening The Activity Ofmentioning
confidence: 99%
“…To simultaneously overexpress multiple genes or interfering RNAs in single cells, several established techniques exist. They are based on different principles such as co-transfection of multiple plasmids, usage of bicistronic vectors containing an internal ribosomal-binding site, infection with retroviruses containing different envelope subtypes, or self-processing peptides ( 47 , 102 ).…”
Section: Approaches To Identify Critical Targets Executing Myc-inducementioning
confidence: 99%